Master S-N curve method to fatigue damage assessment of the high-ply cutter body - Wenfei Liu; Bo Chen; Chao Zhou; Wei Li; Hengji Yu (Scientific Reports)
Abstract At present, the cutting fabric thickness of the high-ply cutter can reach 100 mm, which requires high vacuum pressure resistance performance, and the fatigue reliability of the cutter body is an important indicator of cutting performance. In this paper, the cutter body was analyzed by finite element simulation, the equivalent structural stress and Von Mises stress at key positions were calculated separately. Then, the master S-N curve method and traditional method were used to evaluate fatigue damages at key locations of the cutter body, which are compared and analyzed with the fatigue damage of measured dynamic stress. The results show that the maximum fatigue damage calculated by the master S-N curve method is 0.223, which is the safest. it verifies the effectiveness and reliability of the master S-N curve method in evaluating the fatigue damage of the cutter body. Meanwhile, the fatigue damage of the three measuring points calculated by the three methods is all below 0.5, and it indicates that the design of the cutter body is reasonable. In addition, the master S-N curve method and equivalent structural stress method were first applied to the fatigue damage assessment of high-ply cutter body, which provides an efficient and high-precision approach for the anti-fatigue design of cutter body.